Performance of high-speed train traction motor system in acceleration – cruise mode: theoretical analysis - Tri Widodo; Syamsul Kamar; Hilda Luthfiyah; Eko Syamsuddin Hasrito; Sofwan Hidayat; Meiyanne Lestari; Heru Basuki (International Journal of Power Electronics and Drive Systems (IJPEDS), 2026)
This research is based on the development of a 480-kW traction motor for high-speed train (HST) applications. The performance of the traction motor system will be reviewed theoretically with the focus of the research on operational modes, namely acceleration mode and cruise mode. Motor performance will be reviewed more in-depth related to the development of mathematical models for torque function of time, power function of time and efficiency function of speed. The data used in this study are real data of 480 kW traction motor specifications and synthetic data of HST operations. The results of the traction motor performance analysis show that in the operational conditions of acceleration mode, the traction motor requires power and torque at the beginning reaching 4,838.13 Nm to overcome inertia, friction, aerodynamic force and increase speed. In cruise mode, the speed tends to be stable, so the power and torque decrease to 1,133.24 Nm. The results of the traction motor performance theoretically show that the traction motor can work well for variations in speed and track profile.